(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article examines how digital communication technologies shape moral consciousness in the contemporary information society. The expansion of social media platforms, algorithmic content distribution, and global online interaction has fundamentally altered how individuals perceive moral norms, evaluate ethical behavior, and construct value judgments. Using a qualitative conceptual and socio-philosophical methodology, the study analyzes how digital communication influences moral awareness through processes of visibility, immediacy, and networked discourse. The findings suggest that moral consciousness in the digital age is increasingly decentralized, context-dependent, and shaped by algorithmically mediated exposure to ethical narratives. The article concludes that digital communication does not eliminate moral consciousness but transforms it into a fluid and continuously evolving cognitive-ethical structure.